2020
DOI: 10.3390/ijerph17082920
|View full text |Cite
|
Sign up to set email alerts
|

Mothers Who Take Care of Children with Disabilities in Rural Areas of a Spanish Region

Abstract: The purpose of this research is to describe how the mothers of children with disabilities in rural areas of Extremadura perceive care tasks and the subjective impact that these tasks have on their daily life and health, as well as the subjective assessment that these mothers make of the benefits and services of the Spanish welfare policy. An interpretative paradigm was selected, using a qualitative approach and a phenomenological design. Twelve mothers were included. Data were collected through semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
1
17
1
1
Order By: Relevance
“…Thus, a study that aimed to examine how parents experience their work as caregivers for their child with chronic disability reinforces the mother’s hegemony and significant daily commitment ( 19 ) . The tasks are mainly performed by them, with occasional support from other women in the family, such as grandmothers, while the fathers carry out logistical activities and play with the children ( 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a study that aimed to examine how parents experience their work as caregivers for their child with chronic disability reinforces the mother’s hegemony and significant daily commitment ( 19 ) . The tasks are mainly performed by them, with occasional support from other women in the family, such as grandmothers, while the fathers carry out logistical activities and play with the children ( 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Interviews were backed up with other field research techniques ( Table 2 ), such as informal interviews with different agents in the area―i.e., shop attendants and street sellers, individuals from the area who had not fulfilled the initial inclusion criteria, and key agents; direct observation in the spaces for food acquisition in the chosen localities and in the respondents’ own homes and vegetable plots; and a field diary that provided additional information on specific contexts and issues, allowing us to build a more comprehensive picture of the participants [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data and empirical materials regarding the ethnographic fieldwork (phase 1) will be collected through in-depth semi-structured interviews, and participant observation in the field. A field diary will allow to build up a more comprehensive image of subjects through providing additional information on specific contexts and issues [43,44]. All research techniques are shown in Table 1.…”
Section: Data Collection and Measuresmentioning
confidence: 99%